Effect of Nigella sativa on Growth and IGF-1 levels in Rats Prenatally Exposed to Pesticides - Wibowo, Joko Wahyu; Fasitasari, Minidian; Yuniarti, Heny; Tanry, Selvina (Faculty of Medicine, Universitas Padjadjaran, 2025)
Nigella sativa contains antioxidants and can potentially improve growth disorders due to prenatal pesticide exposure. Pesticides affect the work of thyroid hormone, insulin, and Insulin-like Growth Factor that play essential roles in the growth and development processes. This study aimed to determine the effect of Nigella sativa supplementation on body weight and IGF-1 levels in mice, with a history of pesticide exposure in the womb. This study was conducted from October 14, 2023 to December 1, 2023 at the laboratory of the Center for Food and Nutrition Studies, Inter-University Center, Gajah Mada University, Indonesia. This experimental study used a cohort design and involved 20 pregnant female rats as the experimental animals. These rats were divided into several groups: K0 (control group with standard feed), K1 (group exposed to pesticides during pregnancy), and P1 and P2 (group exposed to pesticides. Followed by 10.8 mg/200gBW/day and 21.6 mg/ 200 gBW/day of Nigella sativa after birth, respectively). The pesticide dose used was 10 mg/200gBW/day orally. Anthropometric examinations was conducted at birth, and on day 7, day 14, day 21, and day 28. The examination of IGF-1 levels was performed on day 28 using the ELISA method. Results showed that the mean birth weights (g) of the rats by group were as follows: K0:6.09±0.12; K1:4.03±0.03, P1:4.03±0.02 P2:4.05±0.03. On day 28, the mean body weights (g) were as follows: K0:104.0±1.79; K1:65.17±1.47; P1:92.17 ± 3.19; and P2:102.00±1.41. The mean IGF-1 level (pg/mL) were as follows: K0:23.76±0.68; K1:9.03±0.24, P1:14.94±0.37; and P2:19.51±0.56. The ANOVA test presented a p-value of <0.001. Hence, Nigella sativa supplementation after birth significantly affects body weight and IGF-1 levels in rat model of prenatally exposed to pesticides.